An integrated connectivity risk ranking for phosphorus and nitrogen along agricultural open ditches to inform targeted and specific mitigation management - Opoku, D. G.; Healy, Mark G.; Fenton, Owen; Daly, K.; Condon, T.; Tuohy, Patrick (Frontiers Media, 2024)
On dairy farms with poorly drained soils and high rainfall, open ditches receive nutrients from different sources along different pathways which are delivered to surface water. Recently, open ditches were ranked in terms of their hydrologic connectivity phosphorus (P) along the open ditch network. However, the connectivity risk for nitrogen (N) was not considered in that analysis, and remains a knowledge gap. In addition, the P connectivity classification system assumes all source-pathway interactions within open ditches are active, but this may not be the case for N. The objective of the current study, conducted across seven dairy farms, was to create an integrated connectivity risk ranking for P and N simultaneously, to better inform where and which potential mitigation management strategies could be considered. First, a conceptual figure of known N open ditch source-pathway connections, developed using both the literature and observations in the field, was used to identify water grab sampling locations on the farms. During field work, all open ditch networks were digitally mapped, divided into ditch sections, and classified in terms of the existing P connectivity classification system. Sampling was conducted during the hydrologically-active period to ensure maximum connectivity of source-pathways and open ditches. The results from these water samples enabled a qualitative validation of N source-pathway presence or absence for each ditch category. The results showed that not all source-pathways were present across ditch categories for all species of N. This information was used to develop an improved open ditch connectivity classification system. Results showed that farmyard connection ditches were the riskiest for potential point source losses and outlet ditches had the highest connectivity risk among the other ditches associated with diffuse sources. Tailored mitigation options for P and N speciation were identified for these locations to intercept nutrients before reaching receiving waters. Furthermore, in ...